2021
DOI: 10.21203/rs.3.rs-924042/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrimination of Heavy Metal Sources in the Sefidrud Delta Coastal Lagoons, Caspian Sea, N Iran: A Statistical Approach

Abstract: Amirkola (more than 500 years in age), Kiashahr and Zibakenar (a few decades in age) lagoons are located on the Sefidrud Delta, the southern coast of the Caspian Sea. Evaluating the pollution degree caused by heavy metals (including Cu, Cr, Co, Ni, Pb, Zn and V), 106 sediment samples and three sediment cores were taken from studied lagoons. Three indices, including geo-accumulation index (Igeo), contamination factor (CF), and pollution load index (PLI), were employed to determine the contamination degree in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…40 However, the extracts of some plants have been reported to act as nonionic surfactants but the existing large amount of alkali metal such as Na + and Ka + in Rosmarinus extract and RNH 3 + Cl − radical in henna leaf extract forces them to behave as cationic surfactants. 94,95 Cationic surfactants from different natural plants have been reported that satisfy the EOR requirement with reasonable properties and acceptable CMC value.…”
Section: Classification Of Natural Surfactantmentioning
confidence: 99%
“…40 However, the extracts of some plants have been reported to act as nonionic surfactants but the existing large amount of alkali metal such as Na + and Ka + in Rosmarinus extract and RNH 3 + Cl − radical in henna leaf extract forces them to behave as cationic surfactants. 94,95 Cationic surfactants from different natural plants have been reported that satisfy the EOR requirement with reasonable properties and acceptable CMC value.…”
Section: Classification Of Natural Surfactantmentioning
confidence: 99%